2023
DOI: 10.3390/ani13030439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplementation with Bee Pollen and Propolis on Growth Performance and Serum Metabolites of Rabbits: A Meta-Analysis

Abstract: The objective of this study was to evaluate the effects of bee pollen (BP) and propolis (PRO) supplementation on rabbits’ productive performance and serum metabolites through a meta-analysis. Sixteen peer-reviewed publications were included in the data set. The rabbit strains used in the studies included in the data set were New Zealand White, V-line, Rex, and V-line crosses. Weighted mean differences (WMD) between treatments supplemented with BP or PRO and control treatments were used to assess the magnitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Furthermore, Attia et al [64] found that propolis with bee pollen significantly increased does' litter size (~39%) and milk yield (~43.5%), while decreased feed intake (~4.5%), as well as increased plasma total protein (~43%), albumin (~45.5%), and globulin (~40%). In the same manner, Sierra-Galicia et al [65] reported that diets enriched/supplemented with propolis and bee pollen increased rabbits' weight gain and total antioxidant capacity in blood serum while decreasing feed conversion rate. Aromatic acids, flavonoids, and phenolic compounds are the major substances that interact with the biological features of propolis [66,67].…”
Section: Potential Effects Of Bee Products On Poultry and Rabbit Perf...mentioning
confidence: 77%
“…Furthermore, Attia et al [64] found that propolis with bee pollen significantly increased does' litter size (~39%) and milk yield (~43.5%), while decreased feed intake (~4.5%), as well as increased plasma total protein (~43%), albumin (~45.5%), and globulin (~40%). In the same manner, Sierra-Galicia et al [65] reported that diets enriched/supplemented with propolis and bee pollen increased rabbits' weight gain and total antioxidant capacity in blood serum while decreasing feed conversion rate. Aromatic acids, flavonoids, and phenolic compounds are the major substances that interact with the biological features of propolis [66,67].…”
Section: Potential Effects Of Bee Products On Poultry and Rabbit Perf...mentioning
confidence: 77%
“…The enhancing effects of BP on digestion-related functions in the digestive tract have also been reported by in vivo studies. A very recent meta-analysis reported that BP supplementation to rabbits resulted in an increased activity of digestive enzymes (protease, amylase, and lipase) in the intestinal content, and in an enhanced digestibility of crude proteins, crude fibers, and other organic matter [ 217 ].…”
Section: Resultsmentioning
confidence: 99%
“…In animal models, the anti-atherosclerotic effect of BP ethanolic extracts was verified through diverse markers, including a marked decrease in atherosclerosis biochemical markers, such as total cholesterol, oxidized low-density lipoprotein, asymmetric di-methylarginine, angiotensin-converting factor, and angiotensin-converting enzyme, as well as an overall reduction in atherosclerotic plaques [ 16 , 32 , 100 ]. Accordingly, whole BP supplementation in rabbits resulted in a significant decrease in cholesterol and total lipids, as well as in other biochemical parameters that are closely related to atherosclerotic and myocardial infarction risk, such as lipid peroxidation byproduct malondialdehyde, and the infarct marker aspartate aminotransferases [ 217 ].…”
Section: Resultsmentioning
confidence: 99%
“…The treatment with propolis significantly reduced the ALT compared to the control group (El-Hanoun et al, 2007;Zeweil et al, 2016 b). Likewise, reduced serum levels of AST, ALT, and malondialdehyde were detected in response to propolis supplementation in the diet of rabbits (Sierra-Galicia et al, 2023). On the other hand, no significant effects have been detected on AST or ALT due to propolis supplementation to broilers diets (Tatli Seven et al, 2009;Attia et al, 2014 b).…”
Section: Blood Parametersmentioning
confidence: 98%
“…Dosoky et al (2022) demonstrated that the serum total antioxidant capacity was significantly enhanced in broiler chickens supplemented with 100 and 200 mg propolis/ kg diet when compared with chickens supplemented by 300 mg and tylosin, however serum lipid peroxide concentrations were significantly reduced in the groups received 400 mg propolis and tylosin as compared to other groups. In rabbits, supplementation with bee pollen and propolis improved the antioxidant status (Sierra-Galicia et al, 2023).…”
Section: Antioxidant and Anti-stressmentioning
confidence: 99%